(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article reflects on the great scholar and thinker grandfather Abu Abdullah Muhammad bin Musa Khorezmi who lived on our land. The great person is admired not only as a mathematician, but also as a philosopher and a poet. In the words of Islam Karimov, the first President of the Republic of Uzbekistan: "Today, as we look at the great achievements of mankind in the field of science and modern technologies, our hearts are filled with pride that the Uzbek people, like our great grandfather, have a worthy contribution in achieving such high goals." In this article, what periods the Eastern Renaissance includes, at the same time, the names of the bright representatives of the Eastern Renaissance of the 9 th-11th centuries: Narshahi, Farabi, Ibn Sina, Beruni, Mahmud Kashgari, Yusuf Khos Khajib are mentioned with special attention. We found it permissible to talk about our thinker grandfather Abu Abdullah Muhammad bin Musa, who reached the pinnacle of science with his great contribution to the development of science, enlightenment and spirituality, and his prolific creativity.